STUDY ON THE CLINICO-EPIDEMIOLOGICAL PROFILE AND THE OUTCOME OF SNAKE BITE VICTIMS IN A RURAL HEALTH CENTRE IN KANCHEEPURAM DISTRICT, TAMILNADU. - DR. P. MOHANKUMAR,; DR. C. SIVAGURUNATHAN,; DR. R. UMADEVI, (International Journal of Pharma and Bio Sciences, 2015)
Snakebite is an acute medical emergency faced commonly by rural populations in tropical and subtropical countries with heavy rainfall and humid climate. Over 2,000 species of snakes are known worldwide, of which around 400 are poisonous. Elapidae, Viperidae, Hydrophiidae and Colubridae are the major group in which all of these poisonous snakes belongs to.Lot of things remains unknown about snakebites in India. There is a Knowledge gap still exist in the community about the poisonous snakes and their bites. The Indian government has recently adopted the World Health Organization reported that a huge proportion of injuries and death due to snake bites were due to unrecognized poisonous snakes. This study was carried out to describe the epidemiology, arrival delays, clinical patterns, complications, and the outcome of snakebites which were seen in rural health center of Kancheepuram district, Tamilnadu. Statistical analysis: Proportions. A total of 164 cases of venomous snakebite cases were included in this study, who had reported to the rural health center from January 2013 to December 2013. In this study sample, a majority of snake bite victims were aged between 25-45 years with mean age is 28. Most of the cases were males (59.1%) compared to females (40.9%). A majority of the patients were leather workers (51.22%) and tanners (36.58%) and 64 patients (39.02%) were illiterates. The biting species was identified only in 130 cases and the commonest species was Russell’s viper (68 cases), followed by cobra (42 cases) and common Krait (20 cases). The most frequently bitten site was the lower extremity (51.21The incidence of the complications like acute renal failure, gangrene at the bite area, DIC and ARDS were more in the subgroup of patients who presented to the hospital after a delay of >6 hours. No fatal outcome was reported in the victims who were admitted within 24 hours of the snake bite, thus suggesting the importance of an early specific treatment.